Pengaruh Filsafat Yunani Terhadap Ilmu Kalam Dan Implementasinya Pada Materi Pembelajaran Ilmu Kalam Di Madrasah Aliyah - Maharani, Eneng Komariyah Maimun Ratna Ningrum; Sauri, Sofyan; Khalid, Shofa Musthofa (Universitas Cokroaminoto Yogyakarta, 2022)
Philosophy is a science that can never be separated from human life without exception. Philosophy comes from the Greek words Philos which means love and Sophia or Shopos which means knowledge or wisdom. Philosophy is very developed, especially Greek philosophy which gave birth to the great philosophers in the world to be able to influence Islamic philosophy. However, because there are so many pros and cons regarding this influence, several things need to be emphasized so that there are no misunderstandings. The purpose of writing this article is to determine the influence of Greek philosophy on Islamic philosophy which is then implemented in the teaching materials of Kalam at the Madrasah Aliyah level. The research method used is literature study. Sources of data used come from books and related journal articles. The results of his research are Greek philosophy has a great influence in the development of Islamic philosophy, but not as the basis or foundation of Islamic philosophy itself. As for what is implemented in the Kalam Science teaching material, it is Islamic philosophy.